Diabetic education in nursing: A Rodgers' evolutionary concept analysis. Issue 4 (2nd June 2021) - Anderson, Gloria; Casasanta, Daniela; Motta, Paolo Carlo; Sacco, Eugenio; Cocchieri, Antonello; Damiani, Gianfranco; Rega, Maria Luisa
Abstract: Aim: This concept analysis aims to clarify the concept of diabetic education in nursing to provide guidance for the further conceptualization and clarification of diabetic education in nursing. Background: Patient education is a fundamental component of diabetes care. Nurses have taken up a major role in educating people with diabetes to manage their conditions. However, the exact meaning of diabetic education in nursing remains challenging. Design: Rodgers' evolutionary method of concept analysis was performed to explore the concept of diabetic education in nursing. Data Source: We conducted a literature search on Cumulative Index to Nursing and Allied Health Literature (CINAHL), MedLine, and PsycInfo for works published until October 2020 using "patient education, " "diabetes, " and "nursing" as key terms. Results: The concept analysis revealed that key attributes of diabetic education in nursing include patient‐centered and interactive approaches, planning, and problem solving. Antecedents related to individuals with diabetes are their backgrounds, needs, and motivations, while the antecedents related to nurses are experience and attitude. Finally, three different consequences of the concept emerged: an increase in knowledge and skills, a behavioral change, and the improvement of clinical outcomes.